Synthesis, profiling and mode of action studies of PanSulfAms as inhibitors of coenzyme a biosynthesis and utilization - Jana, Collins Edward (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.